Liriodenine, An Aporphine Alkaloid From Enicosanthellum Pulchrum, Inhibits Proliferation Of Human Ovarian Cancer Cells Through Induction Of Apoptosis Via The Mitochondrial Signaling Pathway And Blocking Cell Cycle Progression - Noraziah Nordin; Nazia Abdul Majid; Najihah Mohd Hashim; Mashitoh Abd Rahman; Zalila Hassan; Hapipah Mohd Ali (Dovepress, 2024)
Volume :9 (Page: 1437-1448)